Child population in forced displacement situationin Colombia and its manifestations of citizenship - González-Ocampo, Luz Haydeé; Bedmar-Moreno, Matías (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The article presents the preliminary findings of anongoing research on the forced displacement and its incidence in manifestations of citizenship of the displaced children in Colombia. In order to make explicit the manifestations of citizenship in the transit from rural world to the city, we propose give to give the word to the displaced children as an educational action through narratives expressed in brief accounts. The participants of this study are men, women and children, who take refuge in marginal suburbs in the cities and show a citizenship deficient. The narrative provides an account of the personal and collective dimension of those who have endured the impact of violence, for this reason we present this methodology as a form of reconstruction the history of this people.